2015
DOI: 10.1371/journal.pone.0117504
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation Onset Prior to Umbilical Cord Clamping (Physiological-Based Cord Clamping) Improves Systemic and Cerebral Oxygenation in Preterm Lambs

Abstract: BackgroundAs measurement of arterial oxygen saturation (SpO2) is common in the delivery room, target SpO2 ranges allow clinicians to titrate oxygen therapy for preterm infants in order to achieve saturation levels similar to those seen in normal term infants in the first minutes of life. However, the influence of the onset of ventilation and the timing of cord clamping on systemic and cerebral oxygenation is not known.AimWe investigated whether the initiation of ventilation, prior to, or after umbilical cord c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
121
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(134 citation statements)
references
References 46 publications
8
121
0
3
Order By: Relevance
“…Clamping the cord before initiation of respiration results in an acute transient reduction in left atrial filling leading to an abrupt drop in left ventricular output. Delayed “physiological” clamping after lung aeration results in much smoother transition and less bradycardia in animal models [36]. The Australian Placental Transfusion Study randomised 1,600 babies less than 30 weeks’ gestation to immediate (within 10 s) or delayed clamping (after 60 s or more) [37].…”
Section: Delivery Room Stabilisationmentioning
confidence: 99%
“…Clamping the cord before initiation of respiration results in an acute transient reduction in left atrial filling leading to an abrupt drop in left ventricular output. Delayed “physiological” clamping after lung aeration results in much smoother transition and less bradycardia in animal models [36]. The Australian Placental Transfusion Study randomised 1,600 babies less than 30 weeks’ gestation to immediate (within 10 s) or delayed clamping (after 60 s or more) [37].…”
Section: Delivery Room Stabilisationmentioning
confidence: 99%
“…While the benefit of DCC has been attributed to placental transfusion, it is now apparent that there is a much larger potential benefit if cord clamping is delayed until after the lung has aerated. This approach is called physiological-based cord clamping (PBCC) and leads to a more stable hemodynamic transition as preload and cardiac output is sustained and the large disturbances in systemic and cerebral hemodynamics during transition are avoided [5, 10, 32, 33]. …”
Section: The Umbilical Cordmentioning
confidence: 99%
“…Recent experimental studies in preterm lambs demonstrated that clamping the cord after lung aeration prevents the reduction in cardiac output, cerebral perfusion, and cerebral and SpO 2 associated with cord clamping, and as such, less oxygen was needed [10]. The key factor here is the increase in pulmonary blood flow (PBF) that is triggered by lung aeration.…”
Section: The Umbilical Cordmentioning
confidence: 99%
See 1 more Smart Citation
“…DCC improves blood pressure, reduces the need for blood transfusions and the risk of intra-ventricular haemorrhage and necrotizing enterocolitis in preterm infants [9]. Furthermore, DCC maintains oxygenation by sustained placental circulation and is beneficial if spontaneous pulmonary respiration is delayed or impaired [10][11][12][13]. Recently the use of the term 'deferred' cord clamping has been recommended as this suggests a planned policy in contrast to the term 'delayed' cord clamping which may imply that the cord is clamped later than the ideal time [14].…”
Section: Introductionmentioning
confidence: 99%